Central antihypertensive effects of chronic treatment with RB150: an orally active aminopeptidase A inhibitor in deoxycorticosterone acetate-salt rats. Issue 3 (March 2018) - Marc, Yannick; Hmazzou, Reda; Balavoine, Fabrice; Flahault, Adrien; Llorens-Cortes, Catherine
Abstract : Background and objective: Hyperactivity of the brain renin–angiotensin (Ang) system has been implicated in the development and maintenance of hypertension. AngIII, one of the main effector peptides of the brain renin–Ang system, exerts a tonic stimulatory control over blood pressure (BP) in hypertensive rats. Aminopeptidase A (APA), the enzyme generating brain AngIII, represents a new therapeutic target for the treatment of hypertension. We developed RB150, a prodrug of the specific and selective APA inhibitor, EC33. When given orally in acute treatment in hypertensive rats, RB150 crosses the gastrointestinal and blood–brain barriers, enters the brain, inhibits brain APA activity and decreases BP. We investigate, here, the antihypertensive effects of chronic oral RB150 (50 mg/kg per day) treatment over 24 days in alert hypertensive deoxycorticosterone acetate-salt rats. Methods: We measured variations in Brain APA enzymatic activity, SBP, plasma arginine vasopressin levels and metabolic parameters after RB150 chronic administration. Results: This resulted in a significant decrease in SBP over the 24-day treatment period showing that no tolerance to the antihypertensive RB150 effect was observed throughout the treatment period. Chronic RB150 treatment also significantly decreased plasma arginine vasopressin levels and increased diuresis, which participate to BP decrease by reducing the size of fluid compartment. Interestingly, we observed an increased natriuresis without modifying both plasma sodium and potassium levels. Conclusion: Our results strengthen the interest of developing RB150 as a novel central-acting antihypertensive agent and evaluating its efficacy in salt-sensitive hypertension.